Effectiveness of Extractants for Bioavailable Phosphorus in Tropical Soils Amended with Sewage Sludge - Roberta Corrêa Nogueirol; Wanderley José de Melo; Edna Ivani Bertoncini; Luís Reynaldo Ferracciú Alleoni (Applied and Environmental Soil Science)
Urban wastes such as sewage sludge can be an economically viable alternative source for providing macro- and micronutrients to plants in tropical conditions. Sewage sludge is normally rich in phosphorus (P), which is present in soils mainly in organic forms, so that it is very important to establish methods for estimating its availability to plants. This study aimed to test three extractants that simulate P-uptake by maize (Zea mays) cropped in plots after 13 consecutive years of fertilization with sewage sludge, in a cycle of fertilized sugarcane (Saccharum L.) amended with sewage sludge and organic compost. Soil samples were collected at depths of 0–10, 10–20, and 20–40 cm in March 2010 from the two experimental areas. Soil P was extracted via ion exchange resin, Mehlich-I, and 0.025 M H2SO4 and determined via colorimetry. Maize and sugarcane diagnostic leaves were collected in the experiments, subjected to nitric-perchloric digestion, and the leaf-P content was determined via colorimetry. No significant correlations were found between phosphorus extracted from soils and phosphorus concentrations in diagnostic leaves. Resin extracted larger amounts of P in the short-term experiment, while acidic extractants yielded larger amounts in the long-term experiment.